Manajemen Isu oleh Humas PT Telkomsel Indonesia dalam Menangani Gangguan Layanan Jaringan - Duvalio Adnan Zordi; Mohammad Syahrul Ihsan; Nur Azel Rizki Syabani; Ridho Yazhid; Lilik Sumarni (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2026)
Network service disruptions are critical issues that can negatively affect public trust and corporate reputation in the telecommunications industry. As one of the largest telecommunication providers in Indonesia, PT Telkomsel faces significant challenges in managing public issues related to network disturbances. This study aims to analyze how the Public Relations division of PT Telkomsel manages issues in handling network service disruptions in Indonesia.This research employs a qualitative descriptive approach by analyzing secondary data, including literature studies, official corporate communications, and media coverage related to network service disruptions. The findings indicate that PT Telkomsel’s Public Relations implements issue management through several systematic stages, namely issue identification, issue analysis, communication strategy formulation, message dissemination, and evaluation. The communication strategy emphasizes transparency, rapid response, and the use of digital media as the main channel to communicate with the public.Effective issue management enables the company to reduce negative public perceptions and maintain customer trust. This study confirms that strategic and proactive public relations communication plays an important role in managing network service disruption issues and protecting corporate reputation.